2003
DOI: 10.1087/095315103320995050
|View full text |Cite
|
Sign up to set email alerts
|

Professional writing assistance: effects on biomedical publishing

Abstract: The involvement of professional writers in the reporting of scientific research has generated considerable discussion. I reviewed the literature relating to this debate. Some commentators argue that professional writing assistance can inappropriately influence the reporting of research, undermine accountability for the published work, and deceive readers when the professional writer's contribution is not acknowledged. On the other hand, it has been argued that professional writers improve the quality and reada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A systematic review published in 2003 found that there was insufficient research to assess the effects of professional writing assistance on biomedical publishing. 27 Only one other study has evaluated the association of declared medical writing support and the completeness of reporting. 20 This analysis was restricted to a single journal in which there were very few non-industry-sponsored studies and the overall completeness of reporting was high; although articles that declared professional medical writers were more likely to comply with the CONSORT criteria, the effect was small.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in 2003 found that there was insufficient research to assess the effects of professional writing assistance on biomedical publishing. 27 Only one other study has evaluated the association of declared medical writing support and the completeness of reporting. 20 This analysis was restricted to a single journal in which there were very few non-industry-sponsored studies and the overall completeness of reporting was high; although articles that declared professional medical writers were more likely to comply with the CONSORT criteria, the effect was small.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, ghostwriting threatens the very fabric of science and thus the validity of our medical knowledge, and in doing so it jeopardizes patient care'' (Kassirer 2009). According to the second position, ''Potential benefits associated with the use of professional medical writers include improving the quality and readability of articles, leading to enhanced acceptability, speeding the submission process, and educating researchers in writing, editing, and good publication practices'' (Lagnado 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the literature on the effects of professional writing assistance on biomedical publishing identified a number of potential problems associated with the use of professional writers 3 . These included inappro priately influencing the reporting of research, reducing the accountability of a scientific paper, and a lack of openness associated with failure to disclose the contributions of professional writers 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These included inappro priately influencing the reporting of research, reducing the accountability of a scientific paper, and a lack of openness associated with failure to disclose the contributions of professional writers 3 . Although many concerns are based on opinion rather than research evidence, one recent comparison of industry-linked articles coordinated by a medical writing agency and articles not coordinated in this way on the therapeutic uses of sertraline showed significant differences between the two 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation